A Home in Disorder is not a Home: Examining Race in Trinidad and Tobago - Malek Abdel-Shehid (Caribbean Studies Students' Union, 2020)
Among its neighbours, the island nation of Trinidad and Tobago stands out due to its ethnic makeup. The population of most Caribbean nations is mainly of African descent; similar to Guyana, Trinidad and Tobago is evenly divided between Afro-Trinidadians and Indo-Trinidadians. Unlike many of the other Caribbean colonies, Trinidad and Tobago were not extensive plantation economies until much later in the colonial period (Paton 291). This is one of the main reasons why the country presently hosts a proportionately lower Afro-Trinidadian population in comparison to other Caribbean countries. While other ethno-cultural groups reside in the country, the aforementioned groups have dominated the landscape in numbers since at least the early 20th century (United Nations Statistics Division). Afro-Trinidadians are generally descendants of enslaved Africans brought to the Caribbean to serve as plantation labourers; Indo-Trinidadians are generally the descendants of South Asian indentured labourers brought to Trinidad to fulfill the same role following the abolition of slavery in the British West Indies. Trinidad and Tobago's long history of colonial subjugation has bred a modern social hierarchy highly tied to race. Racial categories centered around physical characteristics and created during the colonial period have been instrumental in the development of this social hierarchy. Its institutionalization within the country's modern national political system has resulted in persisting legacies evident throughout modern Trinidadian society. I focus on the island of Trinidad (while still making occasional reference to Tobago) and argue that Trinidadian national unity has been hampered by the foundations laid by the plantation system and consolidated by the modern political system.